2022
DOI: 10.3390/foods11121729
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Reveals Insights into Deterioration of Rice Quality during Storage

Abstract: To determine the changes in the quality of rice during storage, this study investigated the comprehensive metabolomic profiles of Nanjing 9108 (typical japonica rice) and Jianzhen 2 (typical indica rice) varieties in China, using metabolomics. A total of 13 categories of 593 metabolites including lipids (134 species), phenolic acids (78 species), flavonoids (70 species), alkaloids (67 species), organic acids (64 species), amino acids and derivatives (64 species), saccharides and alcohols (44 species), nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…27, 29, 31, 32, and 35) are only related to glycolysis/gluconeogenesis in NJ ( japonica rice), and all of them were up-expressed in NJS. These results corroborate our previous study findings according to which storage increases the sugar metabolism of japonica rice, and accelerates the accumulation of organic acid [ 14 ]. Der Agopian et al [ 43 ] compared the enzyme activity and protein levels related to starch conversion to sucrose in bananas stored at different temperatures.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…27, 29, 31, 32, and 35) are only related to glycolysis/gluconeogenesis in NJ ( japonica rice), and all of them were up-expressed in NJS. These results corroborate our previous study findings according to which storage increases the sugar metabolism of japonica rice, and accelerates the accumulation of organic acid [ 14 ]. Der Agopian et al [ 43 ] compared the enzyme activity and protein levels related to starch conversion to sucrose in bananas stored at different temperatures.…”
Section: Resultssupporting
confidence: 93%
“…Liu et al [ 12 ] found that the changes of glutathione metabolism in rice were closely related to the yellowing of the stored samples. Our previous metabolomics study also found that the glutathione metabolic pathway was enhanced in rice after storage [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations